2008
DOI: 10.1039/b806524a
|View full text |Cite
|
Sign up to set email alerts
|

Fused tetracycles with a benzene or cyclohexadiene core: [2 + 2 + 2] cycloadditions on macrocyclic systems

Abstract: A series of fused tetracycles with a benzene or cyclohexadiene core (2a-h) is satisfactorily prepared by intramolecular [2 + 2 + 2] cycloadditions of triynic and enediynic macrocycles (1a-h) under RhCl(PPh3)3 catalysis; the enantioselective cycloaddition of macrocycles 1b and 1e and gives chiral tetracycles with moderate enantiomeric excess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…Cyclisation of 10 with 1,4-dibromo-2-butyne in the presence of K 2 CO 3 as a base afforded a 60 % yield of macrocycle 3 a. When intermediate 10 was condensed with the dichloro derivative 11 a, previously prepared by us, [8] 25-membered pentaacetylenic macrocycle 4 was obtained with an almost quantitative yield. The p-tolylsulfonamide units give a high level of insolubility in the most common organic solvents in the 20-membered macrocycle.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Cyclisation of 10 with 1,4-dibromo-2-butyne in the presence of K 2 CO 3 as a base afforded a 60 % yield of macrocycle 3 a. When intermediate 10 was condensed with the dichloro derivative 11 a, previously prepared by us, [8] 25-membered pentaacetylenic macrocycle 4 was obtained with an almost quantitative yield. The p-tolylsulfonamide units give a high level of insolubility in the most common organic solvents in the 20-membered macrocycle.…”
Section: Resultsmentioning
confidence: 95%
“…To introduce an arylic unit that was different to the other three and to prepare 3 b, an alternative synthetic route was used (see Scheme 2). Condensation between dichloro derivative 11 b, [8] which introduces the differential aryl unit, and trisulfonamide 12 a [6] afforded a 96 % yield of macrocycle 3 b. Reaction of 12 b [6] with 11 b [8] gave macrocycle 3 c containing four units of 2,4,6-triisopropylphenyl.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In recent years our group has been interested in the synthesis and applications of polyalkyne and enediyne azamacrocyclic systems [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Early on we observed that the [2+2+2] cycloisomerization of the closed derivatives could easily result in highly functionalized tetracyclic fused structures in one-pot and atom-economical process.…”
Section: Introductionmentioning
confidence: 99%